2013
DOI: 10.1097/mlr.0b013e318290216f
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Emerging Safety and Effectiveness Evidence on the Use of Physician-administered Drugs

Abstract: Background Spending on physician-administered drugs is high and uses not approved by the U.S. Food and Drug Administration (FDA) are frequent. While these drugs may be targets of future policy efforts to rationalize use, little is known regarding how physicians respond to emerging safety and effectiveness evidence. Study objective We analyzed changes in bevacizumab (Avastin™) use for breast cancer in response to its market launch (Feb-2008), two FDA meetings reviewing data suggesting that its risks exceed it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Challenges to using FAERS data, however, have been reported to include under-reporting [ 11 , 12 ], the “Weber Effect” [ 13 , 14 ], and “stimulated reporting” [ 15 19 ]. With regard to under-reporting, while it remains a significant limitation, recent efforts by the FDA, global regulatory agencies, and the healthcare industry itself are helping to increase AE reporting rates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Challenges to using FAERS data, however, have been reported to include under-reporting [ 11 , 12 ], the “Weber Effect” [ 13 , 14 ], and “stimulated reporting” [ 15 19 ]. With regard to under-reporting, while it remains a significant limitation, recent efforts by the FDA, global regulatory agencies, and the healthcare industry itself are helping to increase AE reporting rates.…”
Section: Introductionmentioning
confidence: 99%
“…To help guide prescribing decisions and arm healthcare professionals with emerging post-marketing safety risks, the FDA issues warnings [ 7 , 18 , 25 ], which have often effectively modified prescribing behaviors [ 17 , 19 ]. However, the alerts are sometimes challenged by the scientific community [ 17 , 26 – 29 ], numerous alerts can be required to trigger an effect [ 30 ], and too often they have little to no impact on prescribing patterns [ 17 , 28 , 31 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small majority (52 %) agreed with the FDA decision to withdraw the indication on the ground that the benefits shown in the two additional studies with bevacizumab were not of the same amount observed in the initial E2100 trial but 48 % believed this was not a valid reason. Another study examined trends in use of bevacizumab for breast cancer in 122 oncology practices involving 570 oncologists in the US [ 34 ]. It found that the use declined by 37 % between May 2010 (just prior to the ODAC meeting revoking approval) and November 2010 (just prior to the start of the FDA withdrawal process) and by 63 % just prior to the FDA official withdrawal notice without concomitant changes to clinical guidelines or insurers’ coverage policies that may explain these trends.…”
Section: Resultsmentioning
confidence: 99%
“…Bevacizumab (Bev) was the first vascular endothelial growth factor (VEGF)-A inhibitor to be studied in breast cancer and other solid cancers (1014), and is currently approved by the USA Food and Drug Administration (FDA) for use in several cancer types (1214). Following provisional approval for use in metastatic breast cancer in the USA, the FDA subsequently revoked approval in November 2011, due to the risks of Bev therapy outweighing the benefits (15,16). Currently, Bev is only approved for the treatment of breast cancer outside the USA.…”
Section: Introductionmentioning
confidence: 99%